RELASI SUAMI DAN ISTRI: PEMIKIRAN AMINA WADUD MUKSIN TERHADAP Q.S AN-NISĀ' [4]: 34 - Irfan Fajar Ramadh (Tanzil: Jurnal Studi Al-Quran, 2021)
Amina Wadud is a feminist figure who intensively interprets gender verses in the Qur'an. She is a figure who supports the existence of hermeneutics in the study of interpretation. She is heavily involved with issues related to gender and feminist issues. Therefore, it is not surprising that she is considered one of the leading Muslim feminists. As a feminist figure, she has criticized many methods of religious understanding that discriminate against women, especially those related to the method of interpreting the Qur'an. For this reason, he concluded that it was necessary to reinterpret the Qur'an. This research is a literature study (literature study) and focuses on Q.S An-Nisā’ [4]: [34} "Men are leaders for women". As for Amina Wadud's thoughts on the relationship between husband and wife, it is not as a hierarchical relationship pattern but as a function of partnership.